Papan Permainan Puzzle Sebagai Media Pembelajaran Aksara Jawa Pada Anak Usia Dini - Ghazali, Ahmad; Ngabekti, Dhevin Kawistoro; Andriani, Nanda Putri (ISI Press Institut Seni Indonesia Surakarta, 2021)
Javanese, one of more than 300 languages in Indonesia. In order to understand the legacy of our ancestors, the role of the Javanese script is quite significant so it is important to learn and understand. At this time, the interest of early childhood in Indonesian culture is starting to decrease and it can cause Indonesian culture to be abandoned. The low level of ability to read and write Javanese script is due to several factors, namely, interest, teachers, learning methods, and learning media facilities and infrastructure. Applying the Javanese script learning method from an early age using the puzzle game media, it is hoped that future generations will be able to master it and be able to preserve the cultures of this beloved country. The research method chosen is descriptive qualitative by collecting data through a literature study process where data collection comes from books and documents related to the discussion of this article.